2018
DOI: 10.1103/physrevx.8.021055
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Conduction as the Possible Origin of the Electronic Transition in Pentatellurides: Metallic vs Semiconducting Behavior

Abstract: The pentatellurides ZrTe 5 and HfTe 5 are layered compounds with one-dimensional transition-metal chains that show a not-yet-understood temperature-dependent transition in transport properties as well as recently discovered properties suggesting topological semimetallic behavior. Here, we report magnetotransport properties for two kinds of ZrTe 5 single crystals grown with the chemical vapor transport (CVT) and the flux method (Flux), respectively. They show distinct transport properties at zero field: The CVT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
104
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 38 publications
25
104
1
Order By: Relevance
“…The nontrivial Berry phase (~ π) in ZrTe 5-δ was obtained from the Shubnikov with that reported. [41] Not surprisingly, we also observed a sign change in Hall resistance near 135 K accompanied by the change of dominated carrier from n-type to p-type, as shown in Fig. 1(d) and its inset.…”
supporting
confidence: 66%
“…The nontrivial Berry phase (~ π) in ZrTe 5-δ was obtained from the Shubnikov with that reported. [41] Not surprisingly, we also observed a sign change in Hall resistance near 135 K accompanied by the change of dominated carrier from n-type to p-type, as shown in Fig. 1(d) and its inset.…”
supporting
confidence: 66%
“…, was extracted and fitted with the two-carrier model [42], hole carrier starts to appear. The mobility of hole carriers is greater than that of electron carriers, but the density of hole carriers is smaller, thus corresponding to an initial positive slope in ρxy (H) followed by a change to negative, consistent with previous studies [44]. At higher temperature, two hole carriers dominate, and meanwhile the electron carriers disappear.…”
Section: Resultssupporting
confidence: 90%
“…ZrTe5 [44]. The observation of carrier type reversal as temperature increases support the Lifshitz transition.…”
Section: Resultssupporting
confidence: 53%
“…This possibility is verified in a recent experimental work by Shahi et al . They found that the resistance anomaly of ZrTe 5 , which was observed in many existing experiments, is due to the Te deficiency, while the nearly stoichiometric ZrTe 5 single crystal shows the normal semiconducting transport behavior27. In order to avoid the possible artificial effect induced by the cleavage in both STM and ARPES experiments, we suggest that nondestructive optical measurements for the existence of a direct band gap at Γ point, and its change under different temperatures, in the high quality and stoichiometric single crystals are probably useful to elucidate the topological nature in ZrTe 5 and HfTe 5 .…”
Section: Discussionmentioning
confidence: 94%